Advancing insights into virus-induced neurodevelopmental disorders through human brain organoid modelling - Gabriella Crawford; Olivia Soper; Eunchai Kang; Daniel A. Berg (Expert Reviews in Molecular Medicine)
Human neurodevelopment is a complex process vulnerable to disruptions, particularly during the prenatal period. Maternal viral infections represent a significant environmental factor contributing to a spectrum of congenital defects with profound and enduring impacts on affected offspring. The advent of induced pluripotent stem cell (iPSC)-derived three-dimensional (3D) human brain organoids has revolutionised our ability to model prenatal viral infections and associated neurodevelopmental disorders. Notably, human brain organoids provide a distinct advantage over traditional animal models, whose brain structures and developmental processes differ markedly from those of humans. These organoids offer a sophisticated platform for investigating viral pathogenesis, infection mechanisms and potential therapeutic interventions, as demonstrated by their pivotal role during the 2016 Zika virus outbreak. This review critically examines the utilisation of brain organoids in elucidating the mechanisms of TORCH viral infections, their impact on human brain development and contribution to associated neurodevelopmental disorders.